Physiological response and productivity of safflower lines under water deficit and rehydration - Bortolheiro, Fernanda P. A. P. [UNESP]; Silva, Marcelo de Almeida [UNESP] (FapUNIFESP (SciELO), 2017)
Water deficit is one of the major stresses affecting plant growth and productivity worldwide. Plants induce various morphological, physiological, biochemical and molecular changes to adapt to the changing environment. Safflower (Carthamus tinctorius L.), a potential oil producer, is highly adaptable to various environmental conditions, such as lack of rainfall and temperatures. The objective of this work was to study the physiological and production characteristics of six safflower lines in response to water deficit followed by rehydration. The experiment was conducted in a protected environment and consisted of 30 days of water deficit followed by 18 days of rehydration. A differential response in terms of photosynthetic pigments, electrolyte leakage, water potential, relative water content, grain yield, oil content, oil yield and water use efficiency was observed in the six lines under water stress. Lines IMA 04, IMA 10, IMA 14 showed physiological characteristics of drought tolerance, with IMA 14 and IMA 16 being the most productive after water deficit. IMA 02 and IMA 21 lines displayed intermediate characteristics of drought tolerance. It was concluded that the lines responded differently to water deficit stress, showing considerable genetic variation and influence to the environment.
Keywords: Carthamus tinctorius L; Drought physiology; Irrigation; Water use efficiency; Yield